Taxpayers' attitudes toward tax compliance in the Slovenian tax system: differences according to gender, income level and size of settlement (Public Sector Economics - submission site, 2024)
This study investigates the relationship between certain economic and psychological factors and demographic characteristics of Slovene taxpayers, such as gender, income level and size of settlement as it is becoming important for a country’s tax compliance framework to align with the tax recommendations of global institutions. The results show some gender differences, with males being less likely to feel guilty or bad if taxes are not paid in full than females, whereas females tend to have the opinion that working for cash-in-hand payment without paying tax is not a trivial offence. Taxpayers with low incomes tend to agree that tax evasion is morally acceptable if tax rates are too high. Taxpayers from rural settlements exhibit a higher tendency to feel morally obligated to pay their taxes than taxpayers from urban settlements. The findings indicate that the vast majority of taxpayers feel morally obligated to pay their taxes.